الحاجة إلى استبدال نظام الميراث الشرعيّ بالميراث العرفيّ في بلاد يوربا، نيجيريا - Yusuf, S.; Nik Rahim Nik Wajis; Subri, I.; Abdurrazzaq, A. (Universiti Sains Islam Malaysia, 2024)
This research work seeks to bring into view the status quo of the Yoruba customary system of inheritance, which is to some extent opposed to the Islamic legal system of inheritance. This is because it is observed that the Yoruba customary system is characterized by some oppression and injustice. Some eligible persons are being deprived their shares like the woman, children and so on. As it is known that Islamic legal rulings have come to put an end to the Pre-Islamic orders in all affairs, transactions and personal laws, including the inheritance. Allah prescribed them all for mankind to eliminate oppression and establish justice among the individuals and groups in the family and the society. Despite the fact that Muslims are in Majority in Yorubaland, Nigeria, most of the Muslims continue to practice the customary system of Inheritance, where some estates are being neglected and not shared, or enjoyed by the people who are not entitled to them.